PEMAKAIAN ONGGOK FERMENTASI DALAM RANSUM TERHADAP PERFORMA AYAM BURAS PERIODE PERTUMBUHAN - Evi Irawati; Mirzah Mirzah; G. Ciptaan (State Islamic University of Sultan Syarif Kasim Riau, 2016)
The aims of this research was to study the effect of using fermented onggok in ransum to native chicken performance. The design used was completely randomized design (CRD) with 5 treatment i.e : R1 (10%), R2 (15%), R3 (20%), R4 (25%) and R5 (30%) with 4 replications. The ransum was composed with protein (18%) and calorie (2900 kcal/kg). Result of research shows that using fermented onggok had highly significant effect (P< 0.05) towards the feed consumption, body weight gain and feed conversion of buras. It was concluded that using fermented onggok could increase highly body weight at level 15%.